Characteristics of motor vehicle accidents in the Herzegovina Region - Ćeremida-Dragišić, Meliha (Array, 2009)
Summary: Epidemiological studies around the world point to motor vehicle accidents as being one of the leading causes of death. The objective of our study was to analyze some characteristics of motor vehicle accidents in the region of Herzegovina. The study included 226 patients treated at the Clinic for Surgical Diseases and Urology of the University Clinical Hospital Mostar in 2005. A total of 78.3% or examinees were men and 21.7% women. The majority of patients of both sexes were aged between 20 and 30 years. Most of the accidents occurred during autumn and winter months, on weekends and in sunny-dry weather conditions. As expected, most of the hospitalized patients were injured either while driving an automobile or in a pedestrian versus automobile collisions. Of the 226 patients 92.5% admitted to the emergency department and 60.2% were hospitalized. Most of the injured (72.1%) were not under the influence of alcohol at time of the accident. 82.7% of injured were examined by medical personnel at the site within 30 minutes from injury but only 43.0% of them arrived at the hospital within 30 minutes of injury. As most of the injured patients were not under the influence of alcohol at the time of the injury we are of the opinion that more attention in preventing motor vehicle accidents should be directed to speeding and the state of the motorways and vehicles themselves. We propose a large-scale epidemiological study in the Herzegovina region and a review of current road management practices and emergency protocols